2021
DOI: 10.1111/evo.14295
|View full text |Cite
|
Sign up to set email alerts
|

Comparing diversification rates in lakes, rivers, and the sea

Abstract: The diversity of species inhabiting freshwater relative to marine habitats is striking, given that freshwater habitats encompass <1% of Earth's water. The most commonly proposed explanation for this pattern is that freshwater habitats are more fragmented than marine habitats, allowing more opportunities for allopatric speciation and thus increased diversification rates in freshwater. However, speciation may be generally faster in sympatry than in allopatry, as illustrated by lacustrine radiations such as Afric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 118 publications
(302 reference statements)
2
34
0
Order By: Relevance
“…This method is most useful in detecting rate shifts deeper in the phylogeny as BAMM assigns tip diversification rates to whole clades, making statistical assessment difficult. Various evaluations have found that the simpler DR statistic correlates well with BAMM estimates (e.g., Igea & Tanentzap, 2020;Miller, 2021;Title & Rabosky, 2019), and we found it very difficult to run BAMM on such a large phylogeny, as did Igea and Tanentzap (2020). We calculated mean phylogenetic distance (MPD) as the average distance between the 100 top species that contribute to each motif; results are similar to those using DR and are reported in Supporting Information Figure S3.…”
Section: Diversificationsupporting
confidence: 62%
“…This method is most useful in detecting rate shifts deeper in the phylogeny as BAMM assigns tip diversification rates to whole clades, making statistical assessment difficult. Various evaluations have found that the simpler DR statistic correlates well with BAMM estimates (e.g., Igea & Tanentzap, 2020;Miller, 2021;Title & Rabosky, 2019), and we found it very difficult to run BAMM on such a large phylogeny, as did Igea and Tanentzap (2020). We calculated mean phylogenetic distance (MPD) as the average distance between the 100 top species that contribute to each motif; results are similar to those using DR and are reported in Supporting Information Figure S3.…”
Section: Diversificationsupporting
confidence: 62%
“…Higher rates of diversification in freshwater fishes compared to marine fishes have been hypothesized to be shaped by barriers that reduce gene flow (e.g., allopatric processes), but meta-analyses of diversification mechanisms have produced mixed results (Miller, 2021). Our study suggests that major rapids correspond to species boundaries in LCR lamprologines, and therefore appear to be important drivers of speciation processes.…”
Section: Role Of High-energy Rapids In Genetic Divergence Of Lamprolo...mentioning
confidence: 71%
“…However, the mechanisms by which some rivers generate unusually high ichthyofaunal diversity and endemicity remain poorly known. Previous studies have inferred allopatric processes as a primary mechanism driving the separation of lineages within and between rivers (Boschman et al, 2021;Dias et al, 2013;Lujan et al, 2020;Miller, 2021); however, diversification in sympatry or parapatry has also been hypothesized for some groups (Burress et al, 2018;Sullivan et al, 2002) including another cichlid genus in the lower Congo (Alter et al, 2017). In this study, we investigated a previously suggested rapids-driven allopatry hypothesis in the LCR (Alter et al, 2015(Alter et al, , 2017Markert et al, 2010;Schwarzer et al, 2011) using genome-wide SNP data across and within four endemic lamprologine cichlids.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…She repeated her analysis in a 2021 article, this time excluding cichlids. Sure enough, diversification rates for the remaining freshwater and saltwater groups roughly matched (15). Probing deeper, Miller classified the remaining fishes as lake, river, or marine species and compared their diversification rates across habitats.…”
Section: Moving the Needlementioning
confidence: 98%